Liver Transplantation for Pediatric Liver Cancer - Rakesh Sindhi (Cancers, 2020)
Unresectable hepatocellular carcinoma (HCC) was first removed successfully with total hepatectomy and liver transplantation (LT) in a child over five decades ago. Since then, children with unresectable liver cancer have benefitted greatly from LT and a confluence of several equally important endeavors. Regional and trans-continental collaborations have accelerated the development and standardization of chemotherapy regimens, which provide disease control to enable LT, and also serve as a test of unresectability. In the process, tumor histology, imaging protocols, and tumor staging have also matured to better assess response and LT candidacy. Significant trends include a steady increase in the incidence of and use of LT for hepatoblastoma, and a significant improvement in survival after LT for HCC with each decade. Although LT is curative for most unresectable primary liver sarcomas, such as embryonal sarcoma, the malignant rhabdoid tumor appears relapse-prone despite chemotherapy and LT. Pediatric liver tumors remain rare, and diagnostic uncertainty in some settings can potentially delay treatment or lead to the selection of less effective chemotherapy. We review the current knowledge relevant to diagnosis, LT candidacy, and post-transplant outcomes for these tumors, emphasizing recent observations made from large registries or larger series.